Implementation of Teacher Interpersonal Communication on Student Behavior Changes - Iman, Mujhirul; Sufni, Nurul; Putri, Eka Julia; Amanda, Syahfira (LPPPIPublishing, 2024)
This study discusses the Implementation of Teacher Interpersonal Communication on Student Behavior Changes. Communication is an important thing in human life. Of course, positive communication behavior is very important for the formation of student personality and has a very big influence on the success of their education. Student communication behavior has a big psychological influence on learning activities. With the attention of teachers, students will be more active and more enthusiastic in learning because they know that they are not the only ones who want to progress. Because, the good and bad achievements achieved by children will affect them and their further educational development. The method used in this study is using a qualitative method, by interviewing the relevant sources and also conducting observations at the destination. And the results obtained from this study are that interpersonal communication between teachers and students has gone well and can change student behavior for the better. Teachers can do this by communicating in depth with these students, namely by listening actively and not judging students with the aim of knowing and understanding the student's perspective.